A novel methodological framework for the optimisation of post-war social housing developments in the South-eastern Mediterranean climate: Policy design and life-cycle cost impact analysis of retrofitting strategies. (1st September 2021) - Ozarisoy, B.; Altan, H.
Graphical abstract: Highlights: Multi-objective optimisation of residential tower blocks' thermal properties was conducted. Life cycle cost and overheating risk assessment were the objective functions. An energy calibration was developed. 81% of savings related to cooling consumption was achieved. Recommendations for the development of building optimization strategies were presented. Abstract: This study analyses the development of modular building design elements to improve the thermal performance of base case post-war social housing development estates in the southeastern Mediterranean climate, which is subtropical ( Csa ) and partly semi-arid ( Bsh ), before different retrofits are undertaken to optimise each building's energy performance. This study's objective is to develop evidence-based passive cooling retrofit design strategies to improve occupants' thermal comfort and reduce the overheating risk. This empirical study employs the socio-technical systems approach to develop a bottom-up energy policy framework for the residential sector. Its mixed-methods design comprises a questionnaire survey, use of thermal imaging, environment monitoring and determining building optimisation. Furthermore, this study discusses the uncertain input parameters for the building energy simulations that quantitative modelling has adopted to calibrate dynamic thermal simulation findings in conjunction with occupants' socio-demographic characteristics, occupancy patterns, household size and recorded environmental conditions. The results reveal that in the non-retrofitted building, cooling and heating comprised the greatest proportion (73%) of total energy consumption. Applications for six passive cooling design strategies were analysed, and after the life-cycle cost assessment of each was considered, off-site modular building applications were developed. After building optimisation, approximately 81% of savings related to cooling consumption were achieved, which suggests that design, ventilation and servicing strategies combined with passive shading systems can improve energy efficiency and indoor air quality of residential buildings, as recommended by the Energy Performance of Buildings Directives.